Occurrence of Angular Cheilitis Among Dental Patients of Sindh Province: A Cross-Sectional Study (Medical Forum Monthly, 2021)
Objective: To determine the occurrence of angular cheilitis (AC) among private dental patients of Sindh Province.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at various dental clinics of Sindh Province from January 2019 to June 2020 for a period of six months.Materials and Methods: A total of 70 patients diagnosed with angular cheilitis were included in this study, after obtaining the consent from patients, the data was transferred to SPSS version 23 for analysis. The chi-square test was applied in which p value 0.05 was considered significant.Results: In this study, 70 patients clinically diagnosed with Angular cheilitis were participated with a mean age 63.07 and SD ±11.08. The reason for AC was evaluated and the most common reason found in both the genders was poor denture construction 34 (48.57%) followed by loss of vertical dimensions or attrition 19 (27.14%) and nutritional deficiencies 11 (15.71%). The cross-tabulation between reasons of AC with gender showed insignificant findings with a p-value of 0.34.Conclusion: Poor denture fabrication, loss of vertical dimension of prosthesis and nutritional deficiencies were identified as a causative factor. Large sample size is required to obtain meaningful estimate of AC among dental patients